Rural development policies in the Province of Alicante (Spain) - Da Silva Pereira, Claudinei [UNESP]; López, José Daniel Gómez; Hespanhol, Antonio Nivaldo [UNESP] (My University, 2016)
This article discusses the characteristics of the Common Agricultural Policy (CAP) in the European Union and its consequences for agriculture in the Mediterranean area, mainly in the Province of Alicante (Valencian Community - Spain). We also characterize the Relations Program between the Rural Economy Development Activities (LEADER) in the mountain area in the Province of Alicante, its specificities and possible improvements in the diversification of economic activities in the municipalities that have benefited from the program's funding. In addition, due to the diversity of agriculture, we approached the performance of agricultural cooperatives by sector of production activity, which reflect the production structures and the presence of different kinds of farmers in the Province of Alicante. Mediterranean agriculture, based on the climatic and farming characteristics, is crucial to the economy of the municipalities and their integration into the European market.
Políticas de desarrollo rural en la provincia de Alicante (España)
Keywords: Agricultural cooperatives; Alicante; European Union; LEADER; PAC